Examination and Treatment Plan for Comprehensive Patient: Case Report - Azka Rajarizqi Gunawan; Dian Yosi Arinawati (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: The basis of diagnosis is history and examination. The process of diagnosis begins with the collection of patient information and data. An accurate diagnosis can determine an appropriate treatment plan. The purpose of this case report is to describe the treatment plan and the course of treatment in a comprehensive patient case. Case: A 45-year-old male patient complained of pain in the lower back right tooth when chewing. The complaint has been felt since 2 days ago with a pain scale of 6. The tooth previously had a large cavity and gradually decayed on its own. Previously there was no spontaneous pain or swollen gums. The pain is aggravated when chewing food and nothing alleviates the condition. A dentist had never seen the complaint. The patient's dental condition has root residues on teeth 18, 21, 22, 24, 26, 28, 38, and 44, pulp necrosis on teeth 12 and 48, dentin caries on teeth 11 and 23, enamel caries on teeth 17, 16, 27, 34, and 35. There are missing teeth 37, 46, and 47. The Oral Hygiene Index (OHI) has a score of 6.3, and the Plaque Index (PI) has a score of 53.5%. Case Treatment: This patient received Dental Health Education (DHE), medication and extraction of tooth 48, scaling and root planning, dental restoration for tooth 11, and control with evaluation. Results: Treatment was carried out over several appointments, starting with extraction of tooth 48 using inferior alveolaris nerve block technique, scaling and root planning and tooth 11 restoration with class IV GV black using composite at the last visit. Conclusion: The treatment plan was organized and sequenced based on the urgency and chief complaint of the patient. Communication between dentist and patient is necessary to build a good relationship in the long treatment process.